The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1590/s0103-84782010000600008
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses between mature and young leaves of sunflower plants to oxidative stress caused by water deficit

Abstract: RESUMO Os efeitos do estresse hídrico e da reidratação nas trocas gasosas juntamente com alterações na lipoperoxidação e atividade da pirogalol peroxidase (PG-POD) foram estudados em folhas adultas e jovens de plantas de girassol (Helianthus annuus L.) cultivadas em casa de vegetação. O estresse hídrico reduziu a fotossíntese (P N ), a condutância estomática (g s ) e a transpiração (E) nas folhas adultas e jovens. No entanto, a amplitude da redução foi dependente da idade da folha. A concentração intercelular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 27 publications
3
8
1
4
Order By: Relevance
“…However, as for stomatal conductance, Si doses promoted reduction of the stress and it was possible to observe an increment in the values of net photosynthesis up to the estimated dose of 102 mg L -1 , which is interesting because, this estimated photosynthesis value of 14.14 µmol CO 2 m -2 s -1 was slightly lower than the average photosynthesis observed in plants irrigated with 100% ETr (15.2 µmol CO 2 m -2 s -1 ). This effect of water stress had already been reported by Cechin et al (2010), who observed reduction the physiological variables photosynthesis, stomatal conductance and transpiration of sunflower leaves due to water stress. In addition, as observed in other studies (Moro et al, 2015;Teodoro et al, 2015), Si has played fundamental role in the improvement of physiological aspects in plants.…”
Section: Resultssupporting
confidence: 78%
“…However, as for stomatal conductance, Si doses promoted reduction of the stress and it was possible to observe an increment in the values of net photosynthesis up to the estimated dose of 102 mg L -1 , which is interesting because, this estimated photosynthesis value of 14.14 µmol CO 2 m -2 s -1 was slightly lower than the average photosynthesis observed in plants irrigated with 100% ETr (15.2 µmol CO 2 m -2 s -1 ). This effect of water stress had already been reported by Cechin et al (2010), who observed reduction the physiological variables photosynthesis, stomatal conductance and transpiration of sunflower leaves due to water stress. In addition, as observed in other studies (Moro et al, 2015;Teodoro et al, 2015), Si has played fundamental role in the improvement of physiological aspects in plants.…”
Section: Resultssupporting
confidence: 78%
“…Os resultados da presente pesquisa são divergentes dos obtidos por Cechin et al (2010) quando constataram que após seis dias de estresse hídrico, imposto por meio da suspensão total do fornecimento de água, as variáveis fisiológicas fotossíntese, condutância estomática e transpiração nas folhas de girassol foram reduzidas em função do estresse imposto.…”
Section: Resultsunclassified
“…O que contrapõe as informações de Cechin et al (2010) e Carneiro (2011, os quais confirmaram que o potencial hídrico foliar diminuiu à medida que o período de déficit de água aumentou em plantas de girassol, evidenciando que as reduções no potencial hídrico refletem diretamente as mudanças que ocorreram no potencial osmótico decorrentes da restrição hídrica.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…The ability to reduce perspiration allows plants to have better management of available soil water (LARCHER, 2006). Cechin et al (2010) evaluating physiological responses in sunflower plants after six days of water stress, found that smaller stomatal lead to reduced transpiration and increased temperature of the leaf tissue. Freitas et al (2011), analyzing the irrigation management of the castor bean under different soil water stress, found that there were no significant effects for this variable.…”
Section: Resultsmentioning
confidence: 99%